(untitled) (Papeles, 2016)
During the development of human beings, identity plays a very important role, because it characterizes individuals and justifies acting a certain way; the absence of this brings several consequences, among them is the deliberate joiningof a mass behavior. To perform a specific study on the subject, the focus was on groups of people who are fans of the teams Independiente Santa Fe and Millonarios Fútbol Club, but, unlike other followers they are characterized by being alone in a violent environment inside and outside the soccer stadium. The research tool was a survey designed to record possible weaknesses in the construction of personal identity of these young peoples, so it was possible to analyze the impact of lack of identity in young people decision as “hooligans”.